PENGARUH KOMUNIKASI VERBAL DAN NONVERBAL KONSUMEN TERHADAP EMOSI POSITIF PELAYAN A&W RESTORAN PEKANBARU - Prakoso, Agil Syafni; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Communication is one of the most important and complex aspects of human life. Humans are greatly influenced by the communication they do with other humans, both known and unknown. Verbal and nonverbal communication as a stimulus can produce a response in the form of positive emotions. The theory used in this study is the S-R (Stimulus – Response) theory. The purpose of this study was to determine the effect of verbal communication and nonverbal communication on positive emotions, and the influence of verbal and nonverbal communication separately on positive emotions.            This research uses quantitative research methods, with data collection techniques through questionnaires. The population in this study amounted to 112 people, the sample in this study used a census sampling technique. The data analysis method used is multiple linear regression analysis. Data processing and testing uses the Windows version 25.0 of the Statistic Product and Service Solution (SPSS) program.            The results of the study using multiple linear analysis, showed that consumers' verbal nonverbal communication simultaneously had a significant influence on the positive emotions of A&W Restaurant waiters in Pekanbaru by 20.9% which was included in the low level of influence. Partially the verbal communication variable (X1) = 0.005, thus the first hypothesis (H1) is accepted, and the nonverbal communication variable (X2) = 0.001, indicating a significant effect on positive emotion (Y) seen from the significantly smaller value of the two variables. than 0.05, thus the second hypothesis (H2) is accepted. Keyword: verbal communication, nonverbal communication, positive emotions.